Towards a neo-Polanyian approach to money: integrating the concept of debt - Saiag, Hadrien (Economy & Society, 2014)
This paper aims to reconsider Polanyi's approach to money. His best-known writing on money uses is deeply original and presents strong insights that dissociate money from the concept of the market. Polanyi also developed an interesting non-dichotomous understanding of money in hisThe great transformation. However, taken together, these two contributions lead to some unresolved questions: his critique of the orthodox approach to money is ambivalent; his argument to separate payment from account is weak; and, most important, he ultimately makes an incomplete break with the classical real/monetary dichotomy. This paper proposes a distinction between money as a set of instruments and practices and money as a concept, through the integration of John Commons's concept of debt into Polanyi's framework. This reformulation allows us to resolve Polanyi's unresolved questions while preserving his major contributions, and leads to a more complex understanding of money.
Keywords: COMMONS, J.R.; COMMONS, John; Great Transformation, The (Book); debt; debt management; economic anthropology; economic aspects; economics; money plurality; political aspects; theories of money